Genome sequencing and functional genomics in Bacillus subtilis : the expression and roles of the superoxide dismutases and NADH dehydrogenases - Scanlan, Elizabeth (Trinity College (Dublin, Ireland). Department of Genetics, 2002)
The work in this thesis spans genome sequencing of Bacillus subtilis, functional analysis of genes of unknown function and more detailed characterisation of the function and regulation of specific genes. Approximately 0.7% of the B. subtilis genome was sequenced as part of the work for this thesis. The completed genome sequence was published in Nature in 1997 (Kunst et al., 1997). 40% of the predicted open reading frames encoded genes of unknown function and the B. subtilis functional analysis (BFA) project therefore began to gather expression and phenotypic data on 1,275 strains that contained pMUTIN4 insertions into such genes.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin